Two new taxa of Impatiens (Balsaminaceae) from southern parts of Western Ghats, India - Prabhukumar, Konickal Mambetta; Jagadeesan, Raveendran; Prasad, Gopalakrishnan; Nagaraj, Bhagavathi Amma Natarajan Achari; Kumar, Vannaratta Veettil Naveen; Veeralinga, Bhaskar; Balachandran, Indira (Phytotaxa, 2017)
Two new taxa of Impatiens viz. I. mankulamensis sp. nov. and I. panduranganii sp. nov. (Balsaminaceae), are described from the southern Western Ghats, India. Notes on description, distribution, morphological variation and conservation status accompany each description, along with colour photographs.